Wearable Cane and App System for Improving Mobility in Toddlers/Pre-schoolers With Visual Impairment - Ambrose-Zaken, Grace Veronica; FallahRad, Mohamad; Bernstein, Henry; Wall Emerson, Robert; Bikson, Marom (Frontiers in Education, 2019)
Abstract Children with congenital visual impairment (SVI&B) are at greater risk of developing delays in motor and other developmental domains. This report describes a series of experiments conducted to evaluate a novel wearable cane and mobile application system prototype. The wearable cane and application system was tested on ability to a) provide hands-free autonomous arc able to detect obstacles, level & surface changes; b) integrate into indoor/outdoor activities of a specialized preschool for learners with SVI&B; and c) be adopted by families, professionals and learners with SVI&B as a safe mobility solution. Stakeholders and children under five with SVI&B evaluated the prototype system. Results: The project successfully created a hands-free wearable white cane that provided students with SVI&B under age five with next step warning when walking across a variety of terrain. Preschool participants with SVI&B easily adopted the wearable cane into their activities with minimal to no prompting or instruction. The P20 prototype scored well across usability features, including maintaining consistent, hands-free, autonomous arc. The invention of a hands-free mobility tool was a significant outcome of this project. These data support that autonomous arc has the ability to provide developmentally appropriate safe mobility solution for toddlers with SVI&B.